'On water' direct vinylogous Henry (nitroaldol) reactions of 3, 5-dimethyl-4-nitroisoxazole with aldehydes and trifluoromethyl ketones. Issue 19 (12th May 2016) - Zhang, Yong; Wei, Biao-Wen; Zou, Li-Na; Kang, Mei-Lian; Luo, Hai-Qing; Fan, Xiao-Lin
Abstract: An efficient 'on water'-promoted direct catalytic vinylogous addition of 3, 5-dimethyl-4-nitroisoxazole to aldehydes and trifluoromethyl ketones was described, giving Henry (nitroaldol) adducts in excellent yields. The trifluoromethyl tertiary alcohol product could be transformed to the corresponding styrene derivative, which was demonstrated as a new type of Michael acceptor in the vinylogous 1, 6-Michael addition with nitromethane. Graphical abstract: